Léxico e Imagem com inputs da memória afetiva: cognição e emoção em experimentos linguístico-visuais - Dubinskas, Ricardo (2011)
In this study we investigated the amount of number of words stored like memories after processing together perceptions of mental imagery and text, with emotional inputs as triggering agent for one of the surveyed groups and without emotional inputs for a second group. It have been studied the relationships between emotional memories, evoked by images, together with verbal designation of those images and the possible generation of new verbal memories, supported by the reminiscent process. The hypothesis for the study was that the number of words in a foreign language, recorded after his presentation to the subjects with the presence of emotionality as a trigger, is greater than the number of words memorized presented with standard strategies, where the learner moves the look on the picture, and after, on the text, without triggers of emotionality. It was not to reduce the complexity of the set of processes involved in memory, but revealing part of this complexity and its possible consequences. From the work hypothesis it have been studied and reported the amounts of words, in a foreign language, German in that case, unknown to the researched subjects, those are memorized with the use of those two different teaching strategies.